IMPLEMENTASI RELIABILITY CENTERED MAINTENANCE PADA EXCAVATOR PC-800 - M. Burhannudin; Moch. Anshori (Universitas Maarif Hasyim Latif, 2022)
ABSTRAK PT. PPN adalah perusahaan penyewaan alat-alat tambang salah satunya adalah excavator P-800. Permasalahan pada perusahaan adalah tingginya downtime pada komponen-komponen Excavator sehingga mengakibatkan downtime dan menggangu proses produksi pada penyewa. Untuk mengatasi masalah tersebut penulis melakukan rekomendasi perawatan dengan metode RCM dengan harapan dapat menggurangi downtime pada Excavator. Dari hasil dilakukanya penelitian didapatkan 16 komponen kritis yang diantaranya fuel pre filter cartridge, fuel main filter cartridge, pilot filter element, drain filter cartridge, teeth bucket, hydraulic oil filter element, breather element in hydraulic tank, corrosion resistor cartridge, starting motor, boom cylinder line hose, bucket cylinder line hose, water pump, accumulator, arm cylinder line hose, fuel spill hose engine - fuel tank, dan fuel hose feed pump - cooling plate, dan dari penghitungan didapatkan saran interval penggantian komponen yang optimal pada komponen Dan menghasilkan saran untuk mengurangi downtime dan dengan biaya penghematan penggantian komponen Rp. 20.629.592/tahun atau penghematan biaya sebesar 23%. ABSTRACTPT. PPN is a mining equipment rental company, one of which is the P-800 excavator. The problem with the company is the high downtime on Excavator components, resulting in downtime and disrupting the production process for the tenants. To overcome this problem, the author recommends maintenance using the RCM method in the hope of reducing downtime on the excavator. From the results of the research, 16 critical components were obtained which include fuel pre filter cartridge, fuel main filter cartridge, pilot filter element, drain filter cartridge, teeth bucket, hydraulic oil filter element, breather element in hydraulic tank, corrosion resistor cartridge, starting motor, boom cylinder line hose, bucket cylinder line hose, water pump, accumulator, arm cylinder line hose, fuel spill hose engine - fuel tank, and fuel hose feed pump - cooling plate, and from the calculations obtained suggestions for optimal component replacement intervals on components and produce suggestions for reducing downtime and with component replacement cost savings of Rp. 20,629,592/year or a cost savings of 23%. Keywords: RCM, FMEA, Pareto Diagram, and LTA